EMF Model Refactoring based on Graph Transformation Concepts - Biermann, Enrico; Ehrig, Karsten; Köhler, Christian; Kuhns, Günter; Taentzer, Gabriele; Weiss, Eduard (Electronic Communications of the EASST, 2007)
The Eclipse Modeling Framework (EMF) provides a modeling and code generation framework for Eclipse applications based on structured data models. Within model driven software development based on EMF, refactoring of EMF models become a key activity. In this paper, we present an approach to define EMF model refactoring methods as transformation rules being applied in place on EMF models. Performing an EMF model refactoring, EMF transformation rules are applied and can be translated to corresponding graph transformation rules, as in the graph transformation environment AGG. If the resulting EMF model is consistent, the corresponding result graph is equivalent and can be used for validating EMF model refactoring. Results on conflicts and dependencies of refactorings for example, can help the developer to decide which refactoring is most suitable for a given model and why.